Economic Attitudes, Social Attitudes and Their Psychological Underpinnings – A Study of the Finnish Political Elite - Lönnqvist, Jan-Erik; Kivikangas, Matias (Frontiers in Psychology, 2019)
We investigated the relation between economic and social attitudes and the psychological underpinnings of these attitudes in candidates (N = 9515) in the Finnish 2017 municipal elections. In this politically elite sample, right-wing economic attitudes and social conservatism were positively correlated (r = .41), and this correlation was predominantly driven by those on the economic left being socially liberal, and vice versa. In terms of underlying psychological processes, consistent with dual process models of political ideology, the anti-egalitarian aspect of social dominance orientation was more strongly associated with right-wing economic attitudes, and the conventionalism and aggression aspects of right-wing authoritarianism with social conservatism. Our results show that even in a non-US context in which the masses organize their political attitudes on two independent dimensions, these dimensions are moderately aligned among certain parts of the political elite, and that the political attitudes of the political elite can be traced to underlying psychological motivations. We argue that equality concerns could play a role in explaining why the left-right and liberal-conservative dimensions are more strongly aligned among those on the left and those more liberal.